2004
DOI: 10.2527/2004.8213_supple173x
|View full text |Cite
|
Sign up to set email alerts
|

Animal management to reduce phosphorus losses to the environment1

Abstract: Water quality in the United States is threatened by contamination with nutrients, primarily nitrogen and phosphorus. Animal manure can be a valuable resource for farmers, providing nutrients, improving soil structure, and increasing vegetative cover to decrease erosion potential. At the same time, application of manure nutrients in excess of crop requirements can result in environmental contamination. Environmental concerns with P are primarily associated with pollution of surface water (streams, lakes, rivers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
91
0
7

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(102 citation statements)
references
References 73 publications
(120 reference statements)
1
91
0
7
Order By: Relevance
“…20) intake is captured in milk, with the remainder excreted via feces and urine. Dairy manures therefore contain appreciable quantities of N and P in a ratio that is inefficient in meeting crop nutrient needs (20). Applying sufficient manure to fulfill N requirements (as is often practiced), may saturate the soil's P-holding capacity, allowing excess P to transfer into water courses via surface runoff and increasing the potential for eutrophication to occur.…”
Section: Resultsmentioning
confidence: 99%
“…20) intake is captured in milk, with the remainder excreted via feces and urine. Dairy manures therefore contain appreciable quantities of N and P in a ratio that is inefficient in meeting crop nutrient needs (20). Applying sufficient manure to fulfill N requirements (as is often practiced), may saturate the soil's P-holding capacity, allowing excess P to transfer into water courses via surface runoff and increasing the potential for eutrophication to occur.…”
Section: Resultsmentioning
confidence: 99%
“…However in Europe and the United States, where deficiency is unusual, the current emphasis is on diminishing P from dairy operations because P overloading can be harmful to the environment (Nennich and Harrison, 2008). Many studies have shown that dairy cows are often fed more P than they require according to current recommendations (Wu et al, 2001;Valk et al, 2002;Knowlton et al, 2004;Nennich and Harrison, 2008). Manure from dairy cows fed high levels of P has been shown to increase the potential for P runoff losses (Ebeling et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Totally, 70% of P ingested is excreted either via the faeces or via urine. In order to reduce P losses, P supplied to pigs should be adjusted to their requirement, and strategies to improve P availability should be implemented (Poulsen, 2000;Knowlton et al, 2004). This approach relies on an accurate knowledge about feed P availability and P requirement according to the physiological status of pigs.…”
Section: Reduction Of P In Pig Manurementioning
confidence: 99%